(untitled) (Indonesian Art and Justice Review, 2024)
In Indonesia, environmental degradation due to deforestation, mining, and industrialization has sparked a powerful movement of artivism—art that seeks to raise awareness and incite action on environmental justice issues. This paper explores the intersection of art and environmental justice, focusing on how artists in Indonesia use their work to address the country’s environmental crises, including the destruction of natural resources and the displacement of indigenous communities. Through the lens of artivism, the paper examines how artists use visual art, installations, street art, and multimedia to mobilize public opinion, challenge government policies, and promote sustainable practices. By highlighting the role of art in shaping environmental discourse, the paper emphasizes its potential to foster collective action for a more just and sustainable future in Indonesia.